The Impact of Red Blood Cell Distribution Width and Neutrophil/Lymphocyte Ratio on the Diagnosis of Major Depressive Disorder - Demircan, Fatih; Gozel, Nevzat; Kilinc, Faruk; Ulu, Ramazan; Atmaca, Murat (Springer London Ltd, 2016)
Introduction: Major depressive disorder (MDD) is an important risk factor for cardiovascular mortality and morbidity. Red blood cell distribution width (RDW) and neutrophil/lymphocyte ratio (NLR) can be obtained with a basic hemogram test. These parameters have been found as a predictor of mortality in the general population and in several diseases such as cardiovascular disease. Methods: Our study included 100 patients with newly diagnosed MDD and 100 healthy control patients (who had no depressive symptoms and without heart disease) admitted to our outpatient clinics. Patients with MDD were started on selective serotonin reuptake inhibitor (SSRI) treatment and followed up for 3 months. Both MDD and control patients' laboratory tests and physical, neurological, and psychiatric examinations were performed both at diagnosis and after 3 months of treatment. Results: In total, 100 patients with MDD were evaluated and 80 were included in our study. The control group consisted of 91 healthy individuals. The mean age was 44 +/- 10.6 years for patients with MDD and 39.8 +/- 11.4 years for the control group. There was no significant difference between the age for groups (P = 0.13); 55% of patients with MDD and 33% of the control group was male. NLR levels were found to be 2.55 +/- 0.7 and RDW levels were found to be 14.3 +/- 2.6 in patients with MDD; NLR levels were found to be 1.41 +/- 0.8 and RDW levels were found to be 13.4 +/- 1.8 in the control group. RDW and NLR levels were significantly higher in patients with MDD compared to the control group. The significant difference between the levels of RDW and NLR in patients with MDD and the control group was dissolved after SSRI treatment (P < 0.001). RDW [ median 14.3, interquartile range (IQR) 2.8 vs. median 13.25, IQR 2.45; P < 0.001] and NLR (median 2.3, IQR 1.1 vs. median 2.0, IQR 1.15; P < 0.001) levels were significantly higher in patients with MDD compared to the control group. Conclusion: Our study showed that hematological inflammatory markers might be useful parameters that can be used in patients with MDD for coronary artery disease risk. Specifically, RDW and NLR seem to be more hopeful. Advanced, detailed, and larger studies are needed.
Keywords: Coronary artery disease; Major depressive disorder; Mean platelet volume; Neutrophil/lymphocyte ratio; Red cell distribution width